EXPERIMENTAL JUSTIFICATION USE OF WOOD ASH - Veselova, Dana; Tretjakova, Rasma (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
Biomass as a source of energy will reduce dependence on imported fossil fuels, but at the same time, we add value to countries where biomass fuel sources are just beginning to thrive, in addition to providing renewable energy sources. Biomass energy is recognized as an important component in many countries, as future energy scenario and could contribute significantly to the economic, social situation and environmental objectives. Therefore, the emphasis on biomass as an alternative to fossil fuels has increased in recent times. Research has been conducted for the determination of ash wood, wood ash adding soil, wood ash addition of concrete, but to results subdivisions include information on the quantity of wood ash, wood ash for the soil, concrete strength and determination of wood pellets ash compression.